Smartphones as personal digital archives? Recentring migrant authority as curating and storytelling subjects - Georgiou, Myria; Leurs, Koen (Journalism (London, England), 2022)
This article addresses the smartphone as a complicated technology of forced migration: a device that accompanies those who move, but which also records and catalogues digital traces within life contexts of conflict, uprooting, migration and resettlement. We conceptualise smartphones as personal digital archives: migrants’ curation of their own stories on their own portable devices. Personal digital archives, we argue, reflect the migrant gaze and constitute mobile subaltern subjects’ record of forced migration. Inductively learning from fieldwork conducted across five sites over 5 years, we analyse how the personal digital archive records and reflects the mediation of migration in its three dimensions: symbolic, affective and material. By focussing on personal digital archives, we recentre the authority of migrants as witnessing subjects of their own life stories. Their archives as autonomous migrant records provide a powerful basis to reflect upon and potentially contest mainstream western journalism cultures, which too often reduce migration to a spectacle and the migrant to a dehistoricised figure with little agency or voice.